German Model of Corporate Governance and its contribution in the System of Municipal Boxes - Mallma Chuquillanqui, Mayela (2021)
This article deals with corporate governance according to our context, specifically the Municipal Savings Bank System, arises with the intention of contributing, disseminating and deepening this issue, a very important pillar for the long-term growth and sustainability of organizations, public, private and family. An analysis of the origin of corporate governance is made, the models generally adopted internationally by many countries and organizations are mentioned, the same ones that were raised in realities other than ours, mentioning their priorities, characteristics, benefits and weaknesses, then the contribution is made of the German model in the management of the Municipal Savings Bank System in Peru, in order to have a comprehensive appreciation, and conclude that at the Municipal Savings System level the report of this model was successful for its growth, however it is necessary to improve some issues such as: the nomination and independence of the Board of Directors, the appointment of management, consequently the success or failure of adopting a specific model depending on the culture of the Nation where it is applied, the legislation.